Multihop relaying for broadband wireless mesh networks from theory to practice. - Oyman, Ozgur; Laneman, J. Nicholas; Sandhu, Sumeet
We summarize capacity results to show merits of multihop relaying in broadband cellular mesh networks. Under the guidance of these results, we provide design perspectives on relay deployment, spectrum allocation, and end-to-end optimization of certain QoS measures such as throughput, coverage, reliability, and robustness. We conclude with an overview of recent standardization activities and remarks on remaining open problems and design challenges.
Keywords: QoS; Broadband cellular mesh networks; Broadband wireless mesh networks; End-to-end optimization; Multihop relaying; Relay deployment; Spectrum allocation